2016
DOI: 10.1016/j.envint.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The association of urinary polycyclic aromatic hydrocarbon biomarkers and cardiovascular disease in the US population

Abstract: Background Polycyclic aromatic hydrocarbons (PAHs) are potent atmospheric pollutants produced by incomplete combustion of organic materials. Pre-clinical and occupational studies have reported a positive association of PAHs with oxidative stress, inflammation and subsequent development of atherosclerosis, a major underlying risk factor for cardiovascular disease (CVD). The aim of the current study is to estimate the association between levels of PAH biomarkers and CVD in a national representative sample of Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…Soluble organic chemicals (OC), such as polycyclic aromatic hydrocarbons (PAHs), appear to be central to the biological effects from DEPs and other combustion-derived PM, including vascular outcomes [ 8 , 9 , 10 , 11 ]. Levels of urinary PAH biomarkers have been associated with CVD in US adults [ 12 ], and a link between exposure to PAHs and pre-hypertension has been reported in children [ 13 ]. Furthermore, benzo[ a ]pyrene (B[ a ]P), often used as an indicator of PAHs [ 14 ], was associated with blood pressure elevation in coke oven workers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble organic chemicals (OC), such as polycyclic aromatic hydrocarbons (PAHs), appear to be central to the biological effects from DEPs and other combustion-derived PM, including vascular outcomes [ 8 , 9 , 10 , 11 ]. Levels of urinary PAH biomarkers have been associated with CVD in US adults [ 12 ], and a link between exposure to PAHs and pre-hypertension has been reported in children [ 13 ]. Furthermore, benzo[ a ]pyrene (B[ a ]P), often used as an indicator of PAHs [ 14 ], was associated with blood pressure elevation in coke oven workers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biomonitoring of wildland firefighter's exposure to PAHs from fire emissions has been mostly performed during training exercises [11,34,37,38] and typically based exclusively on 1OHPy analysis [31,33,37,38]. Exposure to PAHs has been associated with the development and/or aggravation of lung function reduction, specifically with exacerbations of asthma and chronic obstructive pulmonary disease, some cardiovascular pathologies and cancer [39][40][41]. Excess morbidity and mortality in firefighters have been related with those diseases and some selected site-specific cancers comparatively with general population [42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, accumulating evidence has suggested that cooking meats at high temperature can produce several hazardous chemicals, including heterocyclic aromatic amines (HAAs), polycyclic aromatic hydrocarbons (PAHs), and advanced glycation end products (AGEs) (12)(13)(14), which are known carcinogens or can impact inflammation and insulin sensitivity (15)(16)(17)(18)(19). Cooking temperature, duration, and doneness level can significantly affect the levels of these chemicals in cooked meats (12)(13)(14).…”
mentioning
confidence: 99%